The historical Jesus in recent research - Dunn, James D. G.; McKnight, Scot (Sources for biblical and theological study, 2005)
The solution of thoroughgoing eschatology / Albert Schweitzer -- View-point and method -- Rudolf Bultmann -- The cause and cure of modernization / Henry J. Cadbury -- Against the life-of-Jesus movement -- Martin Kähler -- "I"-sayings Joachim Jeremias / Rudolf Bultmann -- Characteristics of the ipsissima vox / Joachim Jeremias -- Regnum Dei Deus est / Bruce Chilton -- Criteria : how do we decide what comes from Jesus? / John P. Meier -- The past of Jesus in the Gospels / Eugene E. Lemcio -- The tradition / James D.G. Dunn -- The pressing imminence of the end / G. Kümmel -- Abba as an address to God / Joachim Jeremias -- Kingdom redefined : the announcement / T. Wright -- Jesus and the first table of the Jewish law / E.P. Sanders -- The allusive Jesus / Dale C. Allison, Jr. -- From allegorizing to allegorizing : a history of the interpretation of the parables of Jesus / Klyne R. Snodgrass -- Jesus and the Jewish Nation / B. Caird -- Abandoning the unhistorical quest for an apolitical Jesus / Richard A. Horsley -- The Spirit-filled experience of Jesus / Marcus J. Borg -- Son of Man / M. Casey -- The messianic Son of Man : Jesus' claim to deity / Peter Stuhlmacher -- The historical intention of primitive Christian miracle stories / Gerd Theissen -- Jesus and the temple / E.P. Sanders -- The resurrection of Jesus Christ / E.B. Cranfield -- Jesus' readiness to suffer and his understanding of his death / Peter Stuhlmacher -- The history and nature of the earliest Christian belief in the resurrection / Gerd Luedemann -- The judgment and salvation of Israel / Ben F. Meyer -- The Jewish sign prophets / P.W. Barnett -- Pharisees, sinners, and Jesus / James D.G. Dunn -- Jesus and the Golden Rule / S. Alexander -- The Word becomes flesh : Jesus, gender, and sexuality / Amy-Jill Levine -- The message of Jesus and the problem of mythology / Rudolf Bultmann -- The Gospel traditions and early Christological reflection / G.N. Stanton -- The last tabu? the self-consciousness of Jesus / John A.T. Robinson -- The historical Jesus and the theology of the New Testament / Robert Morgan